A linguistic theory of translation : - Catford, J.C. (Oxford University Press, 1965)
This book is based on lectures given in the School of Applied Linguistics at Edinburgh University. It was thus originally intended for an audience of students already fairly well-informed about general linguistics. To make it more acceptable to the general reader, an opening chapter has been added which discusses briefly the nature of language and the categories of general linguistics as well as giving an outline of the analysis and description of English which underlies the discussion of a number of examples. Parts of the book are somewhat technical. This is inevitable in a book on a specialized topic, but it should not dismay the general reader since the main arguments demand little or no previous knowledge of linguistic science and the first chapter may be used for reference when required